Preliminary Investigation of Astragalus arpilobus subsp. hauarensis: LC-MS/MS Chemical Profiling, In Vitro Evaluation of Antioxidant, Anti-Inflammatory Properties, Cytotoxicity, and In Silico Analysis against COX-2 - Sabrina Lekmine; Ouided Benslama; Kenza Kadi; Abir Brik; Ouidad Djeffali; Manar Ounissi; Meriem Slimani; Mohammad Shamsul Ola; Omayma A. Eldahshan; Antonio Ignacio Martín-García; Ahmad Ali (MDPI AG, 2024)
The search results offer comprehensive insights into the phenolic compounds, antioxidant, anti-inflammatory, cytotoxic effects, LC-MS/MS analysis, molecular docking, and MD simulation of the identified phenolic compounds in the Astragalus arpilobus subsp. hauarensis extract (AAH). The analysis revealed substantial levels of total phenolic content (TPC), with a measured value of 191 ± 0.03 mg GAE/g DM. This high TPC was primarily attributed to two key phenolic compounds: total flavonoid content (TFC) and total tannin content (TTC), quantified at 80.82 ± 0.02 mg QE/g DM and 51.91 ± 0.01 mg CE/g DM, respectively. LC-MS/MS analysis identified 28 phenolic compounds, with gallic acid, protocatechuic acid, catechin, and others. In the DPPH scavenging assay, the IC50 value for the extract was determined to be 19.44 ± 0.04 μg/mL, comparable to standard antioxidants like BHA, BHT, ascorbic acid, and α-tocopherol. Regarding anti-inflammatory activity, the extract demonstrated a notably lower IC50 value compared to both diclofenac and ketoprofen, with values of 35.73 µg/mL, 63.78 µg/mL, and 164.79 µg/mL, respectively. Cytotoxicity analysis revealed significant cytotoxicity of the A. arpilobus extract, with an LC50 value of 28.84 µg/mL, which exceeded that of potassium dichromate (15.73 µg/mL), indicating its potential as a safer alternative for various applications. Molecular docking studies have highlighted chrysin as a promising COX-2 inhibitor, with favorable binding energies and interactions. Molecular dynamic simulations further support chrysin's potential, showing stable interactions with COX-2, comparable to the reference ligand S58. Overall, the study underscores the pharmacological potential of A. arpilobus extract, particularly chrysin, as a source of bioactive compounds with antioxidant and anti-inflammatory properties. Further research is warranted to elucidate the therapeutic mechanisms and clinical implications of these natural compounds.